The effectiveness of experiential learning modules in increasing problem-solving ability of new employees - Ken Budiarto, Helmy Gania; Fauziah, Puji Yanti; Purwanto, Nurtanio Agus (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2024)
This research aims to know the effectiveness of experiential learning modules in increasing Problem solving ability of new fresh graduate employee in SDIT Assisi and Sari Asih Hospital. This study employed a quasi-experimental research design that Pre-Post test Control Group Design was utilized in this study's experiment, in which two classes